KEEFEKTIFAN MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE DENGAN PENDEKATAN OPEN ENDED TERHADAP KEMAMPUAN KONEKSI MATEMATIS KELAS VIII MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL - Widia Bilqis Faradila; Dwi Sulistyaningsih; Eko Andy Purnomo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This study aims to determine the effectiveness of the application of Inside Outside Circle learning model with Open Ended approach to the ability of mathematical connections. This research was conducted in MTs Hidayatussibyan Wonosobo and was an experimental research. Sampling with saturated sampling technique. The research population is all students of class VIII with sample of class VIII B and class VIII C. Independent variable used is activity and discipline, as well as dependent variable of mathematical connection ability. Methods of data collection using interviews, documentation, tests, observations, and questionnaires. The results showed that students using Inside Outside Circle learning model with Open Ended approach achieved 80% classical completeness. The influence of student activeness and discipline on mathematical connection ability of 89.00%. The difference of mean value of mathematical connection ability of experimental class is 79,33 better than the average value of control class is 71,59. Based on the research result that the Inside Outside Circle learning model with Open Ended approach on linear equation system material of two class VIII variables can be said to be effective. Keywords: Inside Outside Circle, Open Ended, Mathematical Connection Ability.